Penerapan Ekonomi Sirkular melalui Sistem Pertanian Terpadu Berbasis Zero Waste untuk Meningkatkan Ketahanan Pangan di Desa Sendangtirto, Berbah, Kabupaten Sleman Yogyakarta - Ajat Sudrajat; Djaelani Susanto; Gallusia Marhaeny Nur Isty (Politeknik Pembangunan Pertanian Manokwari, 2025)
Background: The circular economy is one of the best ways to implement an integrated agricultural system based on zero waste to increase food security. This service aims to provide knowledge to the community about the concept of circular economy by utilizing household waste, as a feed material for maggots which later can be used as high-protein feed materials for laying hens and is expected to produce high-omega egg production in Sendangtirto Village, Berbah, Sleman Regency, D.I. Yogyakarta. Methods: This study will be conducted from October 12 to November 6, 2023. This service has been carried out and attended by 20 participants. The implementation method is by providing education and practice directly. The implementation stage began with the distribution of a pre-test questionnaire before the activity, the presentation of material on the introduction of circular economy and integrated agriculture (maggot and laying hen cultivation), the distribution of post test questionnaires to participants and ended with a question and answer session for participants and resource persons. Results: Furthermore, the introduction of feed in the form of household waste and maggots, which can be given with the potential availability in the area. The results of the service show that community knowledge has increased based on post tests and direct practice, so it is hoped that with this education, the people of Sendangtirto Village can utilize waste optimally and can be one of the solutions for processing waste into good feed ingredients to produce omega-rich chicken eggs. Conclusion: It was concluded that the community's knowledge increased, gaining skills in Black Soldier Fly (BSF) maggot cultivation and laying hen cultivation.